PEMANFAATAN GOOGLE FORM UNTUK MENINGKATKAN PEMBELAJARAN BAHASA INGGRIS KELAS VII MTS ASY-SYAFI’IYYAH JATIBARANG - WAWAN ERAWAN (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This Best Practice was prepared to find out the increase in students' understanding and ability in learning English subjects for Class VII MTs Asy-syafi, Iyyah Jatibarang, Brebes Regency during the period from the Covid-19 pandemic to the epidemic. This Best Practice is implemented in the even semester of the 2021/2022 academic year, namely January-June 2021. This Best Practice describes the learning process using Google Form media to support limited face-to-face learning. It is expected that students can improve their learning competencies than before. By using google form media supported by videos and images, it is hoped that the learning will be interesting and can motivate students. Student learning outcomes previously under the Minimum Completeness Criteria (KKM) became even better above the KKM. Before Google Form was applied, 60.6% of students were good at it. After Google Form was applied, the achievement of students' competence in English lessons increased to 80.6% or 20% of completeness. ABSTRAKBest Practice ini disusun untuk mengetahui peningkatan pemahaman dan kemampuan peserta didik dalam pembelajaran mata pelajaran Bahasa Inggris Kelas VII MTs Asy-syafi,iyyah Jatibarang Kabupaten Brebes selama masa dari Pandemi Covid-19 ke edemi. Best Practice  ini dilaksanakan pada semester genap  tahun pelajaran 2021/2022 yaitu bulan Januari-Juni 2021. Best Practice ini menggambarkan tentang proses pembelajaran dengan menggunakan media Google Form mendukung pembelajaran tatap muka terbatas. Diharapkan siswa dapat meningkatkan kompetensi pembelajaranya dari pada sebelumnya  Dengan menggunakan media google form didukung video dan gambar diharapkan pembelajaran tersebut menjadi mertarik dan dapat memotifasi siswa. Hasil belajar siswa yang sebelumnya dibawah Kreteria Ketuntasan Minimal (KKM) menjadi lebih baik lagi diatas KKM. Sebelu diterapkan media google form siswa yang tuntar 60,6 %, setelah diterapkan media google form, pencapaian kompetensi siswa dalam pelajaran Bahasa Inggris meningkat menjadi 80,6 % atau meningkat 20 % ketuntasannya.